Marcadores inflamatórios, cardíacos e expressão de ectoenzimas do sistema purinérgicoem plaquetas de pacientes HIV positivos - Rezer, João Felipe Peres (2016)
Recent studies have demonstrated that HIV infection and antiretroviral treatment may favor a procoagulant state and dyslipidemia, which contribute to developing cardiovascular diseases. Platelets are involved in heart disease,as well as its enzymes, including purinergic system ectoenzymes responsible for the hydrolysis of adenine nucleotides. ATP, ADP, AMP and adenosine are adenine nucleotides and nucleosides that induce different cellular processes such as proliferation, differentiation, chemotaxis, cytokine release, angiogenesis, endothelial cell activation and platelet aggregation. Their extracellular concentrations are controlled by the activity of the enzymes E- NTPDase (CD39), and 5'-nucleotidase (CD73), E-NPP and ecto-adenosine deaminase (E -ADA). Therefore, this study aimed to quantify the proinflammatory and anti-inflammatory cytokines (IL-6, IL-17, IFN-gamma, TNF, IL-10, IL-4, IL-2); and cardiac markers (troponin, LDH, CK, CK-MB, PCR); evaluate the ectoenzymes activity and expression in platelets of HIV-positive patients, thus verifying the importance of purinergic signaling in thromboregulation, and immune and inflammatory responses. , Platelet aggregation, lipid profile and in vitro activity of these ectoenzymes using close to therapeutic doses were also evaluated. The study included HIV-positive patients followed up at the infectious diseases clinic at HUSM. The results showed changes in ectoenzymes (E-NTPDase, E-5'-nucleotidase and E-ADA) activity in platelets without changes in expression. The hydrolysis of ATP was altered in the HIV group when compared to the control group. Regarding the hydrolysis ADP, lower activity was observed in HIV-HAART group compared to the control group. The HIV-HAART group compared with the HIV group decreased 1.2 times the hydrolysis of ADP. Enzymatic hydrolysis of AMP increased by 53% in the HIV group compared to the control group. Between the control group and HIV HAART there was no significant difference in the hydrolysis of AMP. E-ADA showed a reduction of 49.6% in its activity in HIV HAART group compared with the control group. It was also observed a reduction of 34.8% in the activity of E-ADA compared the HIV group with the control group. There was no significant difference between HIV HAART and HIV groups in the E-ADA activity. The platelet aggregation of these patients revealed it was increased by 26% and 40% using the agonist ADP (P<0.05). Changes in the lipid profile, with an increase in serum levels of LDL cholesterol, reduced HDL cholesterol and high triglycerides were observed in the group of HIV- positive patients under antiretroviral therapy. These patients had an increase in serum IL-6 and IFN-gamma with no changes in specific cardiac markers; with the exception of C-reactive protein (CRP) which is also an inflammatory marker. There was no significant change in the in vitro activity of platelet ectoenzymes when incubated with antiretroviral drugs. The results suggest that ectoenzymes purinergic system are involved in the process of thromboregulation in HIV positive patients. In addition, these results indicate changes in inflammatory, and platelet aggregation lipid profiles that may concur to the development of cardiovascular diseases. The parameters reported in this study may be useful in the identification of cardiovascular risk, monitoring of the disease and monitoring the evolution of antiretroviral treatment in their chronic use.